Comparison of a novel cholesterol efflux assay using immobilized liposome-bound gel beads with the conventional method. Issue 8 (4th August 2020) - Horiuchi, Yuna; Lai, Shao-Jui; Kameda, Takahiro; Tozuka, Minoru; Ohkawa, Ryunosuke
Abstract: Cholesterol efflux capacity (CEC) is an atheroprotective function of high-density lipoprotein (HDL). CEC is currently measured using artificially prepared foam cells composed of cultured macrophage and 3 H-cholesterol. However, this conventional method is not suitable for clinical laboratory use due to poor repeatability, complexity, and low safety. Recently, we reported a novel CEC assay, called the immobilized liposome-bound gel beads (ILG) method. The ILG method is an alternative to foam cells, comprising gel beads and 4, 4-diflioro-4-bora-3a, 4a-s-indacene labeled cholesterol (BODIPY-cholesterol) instead of macrophage and 3 H-cholesterol, respectively. The ILG method has shown adequate basic properties and strong correlation with the conventional method. Here, we aimed to compare this new ILG method with the conventional method in-depth. When apoB-depleted serum was used as the cholesterol acceptor (CA), the ILG method had far better reproducibility than the conventional method. The CEC of major HDL subclasses HDL2 and HDL3 had similar results in both the ILG and conventional method. However, the ILG method did not reflect the CEC of apolipoprotein (apo) A–I and a minor HDL subclass which uses ATP-binding cassette transporter A1 on foam cells. Superior reproducibility of the ILG method, which is a limitation of the conventional method, and similar CEC results for major HDL subclasses in the ILG and conventional methods, provide further evidence that the ILG method is promising for measuring CEC clinically. However, some HDL subclasses or apo might have poor CEC correlation between these methods. Further research is therefore needed to confirm the clinical significance of estimating CEC by the ILG method.